Relationship of the airway size to the mandible distance in Chinese skeletal Class I and Class II adults with normal vertical facial pattern - Alqassam Firwana; Hua Wang; Lian Sun; Jialu Wang; Wei-Bing Zhang (Wolters Kluwer Medknow Publications, 2019)
Objective: This study aims to evaluate the pharyngeal airway dimensions among Chinese adults in relation to Class I and Class II facial skeletal patterns using three-dimensional cone-beam computed tomography (CBCT) images. Materials and Methods: A total of 156 initial CBCT images were evaluated, which were classified into skeletal Class I and Class II according to ANB angle with mean (SD) age being 22.56 ± 4.0 years and 22.32 ± 3.6 years. The pharyngeal airway volume, airway area, minimum cross-sectional area (MCA) and the distance from uvula (tip of the soft palate) to mental spine (U-MS distance) were assessed with Dolphin imaging software. Results: Compared with Class I group, Class II group displayed significantly smaller pharyngeal airway volume, airway area and MCA (P <.01, P =0.03, and P =0.008, respectively), and shorter U-MS distance (P <.001). Comparing gender subgroups, the female subgroup showed the smallest airway measurement. Spearman correlation test results showed that the airway volume and area had a significant positive correlation with U-MS distance (r = 0.22, P = 0.005, and r = 0.28, P < 0.005, respectively) and negative correlation with ANB angle (r = −0.23, P = 0.002, and r = −0.21, P = 0.007, respectively). Conclusions: Pharyngeal airway volume, airway area, MCA, and the U-MS distance were smaller in skeletal Class II than Class I Chinese adult subjects and lower in female Class II subgroup. Additionally, there was a correlation observed between the mandibular distance (U-MS), ANB angle and airway size.